Pengaruh Leverage, Likuiditas, Struktural Modal dan Efisiensi Operasional Terhadap Profitabilitas (Studi Perusahaan Sektor Perbankan di Bursa Efek Indonesia Tahun 2019-2021) - Rifqi In’amul Maula; Nungki Pradita (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2023)
This study examines the effect of leverage, liquidity, capital structure and operational efficiency on profitability. The population in this study were all banking companies listed on the Indonesia Stock Exchange from 2019 to 2021. The sample selection used the purposive sampling method and 126 samples were obtained. The results of the research show that the variables of liquidity and capital structure have an effect on profitability but leverage and operational efficiency have no effect on profitability. The data collection method is done quantitatively and the data processing technique uses multiple linear regression analysis. The data used is obtained from financial reports reported on the Indonesia Stock Exchange and can be downloaded through the idx.co.id website and analyzed using SPSS.